2016
DOI: 10.3892/ol.2016.4231
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic cranial irradiation in 399 patients with limited-stage small cell lung cancer

Abstract: Abstract. The benefit of prophylactic cranial irradiation (PCI) in limited-stage small-cell lung cancer (LS-SCLC) was established in a meta-analysis performed in 1999. Since then, considerable progress has been made in the diagnosis, staging and treatment of LS-SCLC, including chemotherapy and radiotherapy, which led to a longer survival time in patients. Therefore, the magnitude of the benefit of PCI should be re-evaluated. Furthermore, the optimum timing of PCI for LS-SCLC treatment has not been established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Untreated patients with SCLC rapidly succumb to the disease within 2–4 months (4). Patients with limited-stage SCLC are usually treated with chemo- and radiotherapy and with consecutive prophylactic cranial irradiation in the case of intracranial metastasis (5,6), while chemotherapy is the primary choice for patients with extensive-stage disease (7). Despite treatment, patients with SCLC eventually relapse due to resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Untreated patients with SCLC rapidly succumb to the disease within 2–4 months (4). Patients with limited-stage SCLC are usually treated with chemo- and radiotherapy and with consecutive prophylactic cranial irradiation in the case of intracranial metastasis (5,6), while chemotherapy is the primary choice for patients with extensive-stage disease (7). Despite treatment, patients with SCLC eventually relapse due to resistance.…”
Section: Introductionmentioning
confidence: 99%
“…"Early" and "late" PCI groups were separated using the median time interval between the start of primary chemotherapy and the start of PCI. No significant difference was identified between the early and late PCI groups, either in the incidence of brain metastases or the overall survival (19).…”
Section: Timing Of Pcimentioning
confidence: 75%
“…Both studies (17,18) were retrospective, which limits strength of the conclusions provided. A similar inference was provided by another retrospective study that included 399 patients with limited-stage SCLC (19). "Early" and "late" PCI groups were separated using the median time interval between the start of primary chemotherapy and the start of PCI.…”
Section: Timing Of Pcimentioning
confidence: 97%
“…A further 16 and 2 studies reported on PCI and maintenance therapies following induction chemotherapy in first-line SCLC, respectively. Twenty-six studies reported disease functioning scales, most commonly the ECOG performance status (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), or the Karnofsky performance status (31)(32)(33)(34)(35)(36). Demographics of patients from the quantitative studies matched the SCLC patient profile described in the literature (37), whereby patients are likely to be male and over 50 years of age.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Sixteen studies (20,34,35,38,39,55,56,70,(81)(82)(83)(84)(85)(86)(87)(88)) reported LS patients undergoing PCI (Figure 2C). The impact of PCI in improving survival vs patients who did not receive PCI was mixed, with some studies demonstrating an OS/progression-free survival (PFS) improvement [8 studies (20,34,35,38,39,83,85,86)], whilst others showing no improvement or a reduced OS [3 studies (82,84,88)].…”
Section: Limited Stagementioning
confidence: 99%